PENGUATAN KARAKTER PEDULI LINGKUNGAN MELALUI PEMBELAJARAN SENI ECOPRINT SISWA DI SEKOLAH DASAR - nugroho, arief (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
Technological developments have an impact on decreasing environmental quality. The results of observations at SD Negeri 3 Sukoharjo, Wonogiri Regency, showed that many of the plants in the school garden were poorly maintained, waste from food and drink wrappers was left scattered around. There has been a lot of research on strengthening the character of caring for the environment, but it is still limited to the substance of learning and school cleanliness activities. The aim of this research is to describe the strengthening of environmentally caring character through ecoprint artwork at SD Negeri 3 Sukoharjo, Wonogiri Regency. The research uses a qualitative descriptive approach and uses interview and observation instruments for data collection. Researchers used triangulation techniques and sources to test the validity of the data. This research was carried out using interactive data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded that the results of implementing environmentally caring character strengthening through ecoprint artwork at SD Negeri 3 Sukoharjo, Wonogiri Regency are as follows: (1) The character of caring for the environment, the indicator of not using dangerous synthetic dyes, is achieved at 100%. (2) The character of caring for the environment, the indicator of reducing the use of toxic chemicals, reached 66.6%. (3) Environmentally caring character, energy and water saving indicators achieved 100%. (4) Environmentally caring character, indicator of caring for and caring for plants reached 100%. (5) Environmentally caring character, reduce, reuse and recycle indicators reached 75%. In general, SD Negeri 3 Sukoharjo has succeeded in strengthening the character of caring for the environment through ecoprint artwork with a success percentage of 88.32%. Apart from the main aim of strengthening the character of caring for the environment at SD Negeri 3 Sukoharjo, Wonogiri Regency, it turns out that it has another impact, namely being able to awaken the entrepreneurial spirit of students by producing paintings and fabric products with leaf motifs that can have economic selling value.